Redox Property Tuning in Bipyridinium Salts - Burešová, Zuzana; Klikar, Milan; Mazúr, Petr; Mikešová, Michaela; Kvíčala, Jaroslav; Bystron, Tomas; Bureš, Filip (Frontiers in Chemistry, 2021)
Bipyridinium salts are currently very popular due to their perspective applications in redox flow batteries. Hence, we designed and prepared a series of bipyridiniums based on 2,2'-, 3,3'-, and 4,4' bipyridine and 2,2'-bipyrimidine. The straightforward synthesis utilizes commercially or readily available starting compounds and their direct N-alkylation, mostly using 1,3-propanesultone. All eleven target derivatives with systematically evolved structure were investigated by cyclic voltammetry, which allowed elucidating thorough structure-property relationships. The electrochemical behavior depends primarily on the parent scaffold, type of N-alkylation, number of quaternized nitrogen atoms, planarity, counter ion as well as the used media. Two derivatives featuring quasi-reversible redox processes were further tested on rotating disc electrode and in a flow battery half-cell. 4,4'-Bipyridinium derivative bearing two sultone residues showed better performance and stability in the flow half-cell with small capacity decays of 0.09/0.15% per reduction-oxidation cycle, based on the number of the utilized redox processes (one/two).